Work team identification associated with less stress and burnout among front-line emergency department staff amid the COVID-19 pandemic. Issue 1 (27th October 2020) - Sangal, Rohit B; Wrzesniewski, Amy; DiBenigno, Julia; Reid, Eleanor; Ulrich, Andrew; Liebhardt, Beth; Bray, Alexandra; Yang, Elisabeth; Eun, Eunice; Venkatesh, Arjun K; King, Marissa
Abstract : Background: The COVID-19 pandemic has exposed front-line healthcare workers to unprecedented risks and stressors threatening both physical and mental health. Prior work in the military has found that team identification, or the sense that one was a part of a team, can help reduce stress and prevent burnout during prolonged stress. Methods: We conducted repeated cross-sectional surveys embedded within emergency department workflow to understand whether team identification was associated with reduced reports of stress and burnout among front-line workers. Results: During the 10-week study which spanned the first wave of COVID-19, 327 of 431 (76%) front-line healthcare workers responded to at least one round of the survey. Higher team identification was associated with significantly less work stress ( B =−0.60, 95% CI −0.84 to to -0.40, p<0.001) and burnout ( B =−12.87, 95% CI −17.73 to -8.02, p<0.001) in cross-sectional analyses. Further evidence of the protective effect of team identification for work stress ( B =−0.36, 95% CI −0.76 to 0.05, p=0.09) and burnout ( B =−13.25, 95% CI −17.77 to -8.73, p<0.001) was also found in prospective longitudinal evidence. Conclusion: This work suggests work team identification is a key buffering factor against feelings of stress and burnout. Efforts to promote team identification may offer a promising way for leaders to support front-line healthcare workers' well-being during the COVID-19 pandemic. These results can inform ongoing COVID-19 operational and quality improvement initiatives.